2017
DOI: 10.1007/s00221-017-5098-x
|View full text |Cite
|
Sign up to set email alerts
|

Habitual exercise is associated with cognitive control and cognitive reappraisal success

Abstract: Habitual exercise is associated with enhanced domain-general cognitive control, such as inhibitory control, selective attention, and working memory, all of which rely on the frontal cortex. However, whether regular exercise is associated with more specific aspects of cognitive control, such as the cognitive control of emotion, remains relatively unexplored. The present study employed a correlational design to determine whether level of habitual exercise was related to performance on the Stroop test measuring s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 69 publications
2
65
0
3
Order By: Relevance
“…Bernstein et al (2018) further suggested that exercise promotes greater emotional flexibility and thus enhanced adaptability when recuperating from stressful events. The only previous study on habitual physical activity and, specifically, cognitive reappraisal found a positive link between regular exercise and self-reported success in reappraising affective pictures (Giles et al, 2017). Given these promising links with more global and indirect indices of emotion regulation, the present study scrutinized the relationship between habitual physical activity and a specific index of stress coping by reappraisal: individuals' spontaneous capacity to generate alternative appraisals for potential stressors.…”
Section: Stress Coping By Cognitive Reappraisalmentioning
confidence: 95%
See 2 more Smart Citations
“…Bernstein et al (2018) further suggested that exercise promotes greater emotional flexibility and thus enhanced adaptability when recuperating from stressful events. The only previous study on habitual physical activity and, specifically, cognitive reappraisal found a positive link between regular exercise and self-reported success in reappraising affective pictures (Giles et al, 2017). Given these promising links with more global and indirect indices of emotion regulation, the present study scrutinized the relationship between habitual physical activity and a specific index of stress coping by reappraisal: individuals' spontaneous capacity to generate alternative appraisals for potential stressors.…”
Section: Stress Coping By Cognitive Reappraisalmentioning
confidence: 95%
“…1 The required sample size was estimated a priori with G*Power (α = .05, 1−β = 0.80). Effect sizes observed in previous relevant research (f 2 =~.10; Giles et al, 2017;Lott & Jensen, 2016; F I G U R E 1 Conceptual model of the link between habitual physical activity and cognitive reappraisal capacity. The dashed frame indicates hypothesized constructs that are not directly assessed in the present study Shields et al, 2016) suggested a minimum of 81 participants.…”
Section: Participantsmentioning
confidence: 96%
See 1 more Smart Citation
“…Anxiety symptoms and alexithymia are measured using the Beck Anxiety Inventory (BAI) [121] and the Toronto Alexithymia Scale (TAS) [122], respectively. Emotion regulation strategies are measured using the Emotion Regulation Questionnaire (ERQ) [123]; emotion regulation, which has been observed to change in response to exercise [124], is also impaired among individuals with SZ and may predict functioning [125]. We assess subjective well-being using the Satisfaction with Life Scale (SWLS) [126], which has been used in prior SZ studies [127].…”
Section: Bdnfmentioning
confidence: 99%
“…También el valor pedagógico de la Educación Física Infantil es de especial relevancia ya que promueve hábitos de vida saludable y activa mediante el desarrollo de movimientos motores básicos (Carson et al, 2015;Giles et al, 2017) y, además, debido a la conexión entre las capacidades cognitivas del infante y la actividad motora puesto que ambas capacidades progresan simultáneamente. En efecto, la Educación Física es el medio por el cual se pueden favorecer las funciones mentales (Davis et al, 2011) tales como la creatividad (Lupu, 2010), lo que la convierte en el medio más idóneo para propiciar y promover el desarrollo, evolución y adquisición de aprendizajes en Educación Infantil, mejorando el rendimiento académico (Shore et al, 2008).…”
Section: Introductionunclassified